Recent advances in the role of high-salt diet in anti- and pro-cancer progression - Tang, Shiwei; Xu, Juan; Wan, Ping; Jin, Shumen; Zhang, Ying; Xun, Linting; Wang, Jinli; Luo, Mei; Chen, Wenjie; Zuo, Zan; Tang, Hui; Qi, Jialong (Frontiers in Immunology, 2025)
Dietary behaviors significantly influence tumor progression, with increasing focus on high-salt diets (HSD) in recent years. Traditionally, HSD has been regarded as a major risk factor for multiple health issues, including hypertension, cardiovascular disease, kidney disease, cancer, and osteoporosis. However, recent studies have uncovered a novel aspect of HSD, suggesting that HSD may inhibit tumor growth in specific pathological conditions by modulating the activity of immune cells that infiltrate tumors and enhancing the effectiveness of PD-1 immunotherapy. This review focused on the duel molecular mechanisms of HSD in cancer development, which are based on the tumor microenvironment, the gut microbiota, and the involvement of sodium transporter channels. The objective of this review is to explore whether HSD could be a potential future oncological therapeutic strategy under specific situation.